Single-cell in situ mapping of glioblastoma and astrocyte cell lines treated with a carbon dot–mediated riluzole nanotherapeutic agent: a live-cell µFTIR and soft X-ray tomography approach - Dučić, Tanja; Pereiro, Eva; Ninkovic, Milena; Sperling, Swetlana; Rohde, Veit; Fernández-González, Claudia; Algarra, Manuel; González-Muñoz, Elena (BMC Springer Nature, 2025)
Nanoparticle-based drug carriers offer a promising alternative to conventional cancer therapies by enabling targeted delivery and reducing off-target toxicity. Here, we used synthesised and characterised carbon-based nanoparticles derived from 2-acrylamido-2-methylpropanesulfonic acid (AMPS-CDs), demonstrating biocompatibility with both human astrocytes and glioblastoma cells. We assessed their potential to enhance riluzole’s efficacy through synergistic interaction (AMPS-CDs@RZ) using live-cell synchrotron-based FTIR spectroscopy and cryo-soft X-ray tomography to monitor biochemical and structural changes at the single-cell level. While AMPS-CDs nanoparticles alone were non-toxic, the combination with riluzole significantly enhanced cell death in glioblastoma cells, with a significantly lower impact in non-cancerous astrocytes. Treatment with AMPS-CDs@RZ induced significant changes in bio-macromolecules, including DNA, protein conformation, and lipid metabolism. Notably, the treatment triggered nuclear envelope (NE) blebbing in glioblastoma cells, likely due to the interaction of the nanoparticle formulation with the nuclear membrane. This initiated stress signals that disrupted the cell’s inner intracellular membrane system, including the endoplasmic reticulum and mitochondria. To our knowledge, this is the first report linking NE blebbing to this mechanism involving membrane disassembly and nuclear envelope blebbing in riluzole-induced toxicity in glioblastoma is novel, providing a new therapeutic strategy and insights into cellular stress responses. These findings suggest that AMPS-CDs nanoparticles are a promising carrier for riluzole, potentially enhancing the specificity and efficacy of glioblastoma treatments while minimising damage to healthy tissues.
Keywords: Glioma; Riluzole; Carbon dots; Nano-carrier; Glioblastoma; Astrocytes; FTIR; Soft x-ray tomography